Elastic Properties of Lithium Disilicate Versus Feldspathic Inlays: Effect on the Bonding by 3D Finite Element Analysis - Trindade, Flávia Zardo; Valandro, Luiz Felipe; de Jager, Niek; Bottino, Marco Antônio; Kleverlaan, Cornelis Johannes (Wiley, 2016)
Purpose: To determine the elastic properties of five ceramic systems with different compositions (lithium disilicate vs. feldspathic ceramics) and processing methods and compare the stress distribution in premolars in the interface with inlays made with these systems loaded with the maximum normal bite force (665 N) using 3D finite element analysis (FEA). Materials and Methods: The elastic properties of five ceramic restoration materials (IPS e.max Press, IPS e.max CAD, Vita PM9, Vita Mark II, Vita VM7) were obtained using the ultrasonic pulse-echo method. Three-dimensional FEA simplified models of maxillary premolars restored with these ceramic materials were created. The models were loaded with a load at the two nodes on the occlusal surface in the middle of the tooth, 2 mm from the outside of the tooth, simulating a loading ball with a radius of 6 mm. Results: The means values of density (g/cm3), Young's modulus (GPa), and Poison's ratio was 2.6 ± 0.3, 82.3 ± 18.3, and 0.22 ± 0.01 for IPS e.max Press; 2.3 ± 0.1, 83.5 ± 15.0, and 0.21 ± 0.01 for IPS e.max CAD; 2.5 ± 0.1, 44.4 ± 11.5, and 0.26 ± 0.08 for PM9; 2.4 ± 0.1, 70.6 ± 4.9, and 0.22 ± 0.01 for Vitamark II; 2.4 ± 0.1, 63.3 ± 3.9, and 0.23 ± 0.01 for VM7, respectively. The 3D FEA showed the tensile stress at the interface between the tooth and the inlay was dependent on the elastic properties of the materials, since the Vita PM9 and IPS e.max CAD ceramics presented the lowest and the highest stress concentration in the interface, respectively. Conclusions: The elastic properties of ceramic materials were influenced by composition and processing methods, and these differences influenced the stress concentration at the bonding interface between tooth and restoration. The lower the elastic modulus of inlays, the lower is the stress concentration at the bonding interfaces.
Keywords: Dental ceramic; Elastic modulus; Finite element analysis; Inlay; Stress distribution; Tooth restoration